DEVELOPMENT OF CREATIVE PERSONALITY OF PRIMARY SCHOOL STUDENT ON THE BASIS OF PERSONALLY ORIENTED LEARNING - Mayborodyuk Н.Д. (Pedagogy of Higher and Secondary Education, 2022)
In the article the value of the personality oriented method opens up of studies for forming f creative personality ond found out the levels of verbal and vivid creative thought of pupils of 2-5 forms.